Osteocalcin Levels in Male Idiopathic Hypogonadotropic Hypogonadism: Relationship With the Testosterone Secretion and Metabolic Profiles - Yang, Yu-Ying; Zheng, Si-Chang; Wang, Wen-Cui; Yang, Zu-Wei; Shan, Chang; Zhang, Yu-Wen; Qi, Yan; Chen, Yu-Hong; Gu, Wei-Qiong; Wang, Wei-Qing; Zhao, Hong-Yan; Liu, Jian-Min; et al. (Frontiers in Endocrinology, 2019)
Idiopathic hypogonadotropic hypogonadism (IHH) patients are characterized by the absence of puberty and varying degrees of deteriorated metabolic conditions. Osteocalcin (OC) could regulate testosterone secretion and energy metabolism, but it remains unknown whether such an effect exists in IHH patients. Our study is aimed to examine the relationship between serum OC levels with testosterone and its responsiveness to gonadotropin stimulation and metabolic profiles in male IHH patients. A total of 99 male patients aged 18–37 years and diagnosed with IHH were enrolled in the current study, and the relationships between OC and testicular volume, baseline total testosterone (TT), free testosterone (FT), and peak TT (Tmax) levels after human chorionic gonadotropin (hCG) stimulation, gonadotropin responsiveness index (GRI), which is calculated by dividing Tmax by testicular volume, as well as metabolic profiles, such as 2-h post-challenge glucose (2hPG) and fat percentage (fat%), were analyzed. The results showed that OC had an independent negative relationship with testicular volume (r = −0.253, P = 0.012) and a positive association with Tmax (r = 0.262, P = 0.014) after adjusting for confounders. In addition, OC was a major determinant of GRI (adjusted R2 for the model = 0.164, P = 0.012), fat% (adjusted R2 for the model = 0.100, P = 0.004), and 2hPG (adjusted R2 for the model = 0.054, P = 0.013) in IHH patients. In conclusion, OC is associated with testosterone secretion upon gonadotropin stimulation, glucose metabolism, and fat mass variations in IHH. This study was registered at clinicaltrials.gov (NCT02310074).